Integrated Full-Length Transcriptome and MicroRNA Sequencing Approaches Provide Insights Into Salt Tolerance in Mangrove (Sonneratia apetala Buch.-Ham.) - Chen, Beibei; Ding, Zeyi; Zhou, Xiang; Wang, Yue; Huang, Fei; Sun, Jiaxin; Chen, Jinhui; Han, Weidong (Frontiers in Genetics, 2022)
MicroRNAs (miRNAs) are small RNA molecules that serve as key players in plant stress responses. Whereas stress-regulated miRNAs have been explored in various plants, they are not well studied in mangroves. Herein, we combined PacBio isoform sequencing (Iso-Seq) with BGISEQ short-read RNA-seq to probe the role of miRNAs in the salt stress response of the mangrove plant, Sonneratia apetala Buch.-Ham. Totally, 1,702,463 circular consensus sequencing reads were generated and produced 295,501 nonredundant full-length transcripts isoforms from leaf tissues of a 1-year-old S. apetala. After sequencing nine small RNA libraries constructed from control, 1- and 28-d 300 mM NaCl treatments, we identified 143 miRNAs (114 known and 29 novel miRNAs) from a total of more than 261 million short reads. With the criteria |log2FC| ≥ 1 and q-value < 0.05, 42 and 70 were respectively differentially expressed after 1- and 28-d salt treatment. These differential expression miRNAs potentially targeted salt-responsive genes encoding transcription factors, ion homeostasis, osmotic protection and detoxificants-related proteins, reminiscent of their responsibility for salinity adaptation in S. apetala. Particularly, 62 miRNAs were found to be Sonneratia-specific under salt stress, of which 34 were co-expressed with their 131 target counterparts, producing 140 miRNA-target interactions. Among them, 82 miRNA-target pairs exhibited negative correlations and 18 miRNAs targets were categorized into the “environmental information processing” via our KEGG analysis, relating to plant hormone signal transduction (ko04075), MAPK signaling pathway–plant (ko04016) and ABC transporters (ko02010). These results underscored miRNAs as possible contributors to mangrove success in severe environments and offer insights into the regulatory mechanism of miRNA-mediated salt response in S. apetala.